Hardness indices estimation of supporting structure elements of motor bogies of the electric train ED9M - Bondarev, O. M.; Dzichkovskyy, E. M.; Kryvchykov, O. E.; Skoblenko, V. M. (Science and Transport Progress, 2013)
Purpose. The purpose of article is to develop the measures of hardness indices improvement of the supporting structures of motor cars of the electric trains ED9M. Methodology. In order to achieve the above stated aims the following measures had to be done: to develop a finite element model of the supporting structures of the motor bogie of the electric train ED9M, determine parameters of the developed model; perform the calculations to determine the stress-strain state during loads corresponding to different operating conditions with the search of geometric parameters reducing the highest stress levels. Findings. The obtained results of calculations (fields of stress distribution and strains in the elements of the motor bogie frame) from the viewpoint of the strength and stiffness discovered the best geometric parameters of the bearings in the central suspension beams of the electric trains ED9M in the places of load transmission from the car body to the bogie frame. Originality. Based on the developed finite element models and the theoretical and experimental researches the scientifically grounded modernization measures of the construction elements of the central suspension beams for motor bogies of the electric trains ED9M were developed. Practical value. It was developed an engineering solution concerning the measures to improve the strength and stiffness characteristics of the central suspension beams for the motor cars of the electric trains ED9M. It was given to the Ukrzaliznytsya’s professionals to implement them during repairs.